The role of women's empowerment through family income improvement business program in era 4.0 - I Gusti Ayu Ary Ratih; Ni Putu Nina Eka Lestari (Journal of Business on Hospitality and Tourism, 2021)
This study aims to determine the process of implementing women's empowerment through the Business to Increase Family Income program in the industrial era 4.0, as well as to find out the impact of implementing the Family Income Increase Business program on improving family welfare. This research was conducted with a qualitative approach, and through data collection by interview, further analysis was carried out descriptively. The results show that the role of women's empowerment in Tibubeneng Village is in accordance with their understanding, namely the process of obtaining power, strength or ability, and / or giving power, strength or ability from parties who have power to those who are less or powerless. Impact of Women's Empowerment through Family Income Improvement Business Program in Tibubeneng Village, women that have joined Family Empowerment and Welfare Institution and then they are involved in this business unit; they feel very good, effective and helpful not only for women's empowerment institutions in Tibubeneng Village but also personally. This can be seen from the increase in program activities that can be carried out and the addition of training members every year.